2017
DOI: 10.14692/jfi.12.6.209
|View full text |Cite
|
Sign up to set email alerts
|

Waktu Inkubasi pada Derajat Distilasi Kitosan Enzim dan Efektifitas Penghambatannya terhadap Penyakit Antraknosa

Abstract: The use of chitosan as a coating agent of harvested fruits is an alternative method in controlling anthracnose disease (Colletotrichum sp.). This study aimed to obtain an optimal enzymatic chitosan (EC) that hydrolyzed using chitinase from Burkholderia cepacia isolate E76. The optimal incubation condition to produce EC was 2 h with the yield of 3.52 ± 0.38 g. The degree of deacetylation (DD) chitosan and  EC was 66.91% and 80.91%, respectively. Based on in vitro assays, EC 2% was the most effective in inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…It was also reported that the hydrolyzed chitosan using chitinase produced by B. cepacia isolate E76 at concentration of 2% showed as the most effective treatment in inhibiting the growth of Colletotrichum sp. (94.22%) than that of non-hydrolyzed chitosan (Suryadi et al 2016).…”
Section: Cultivationmentioning
confidence: 85%
See 1 more Smart Citation
“…It was also reported that the hydrolyzed chitosan using chitinase produced by B. cepacia isolate E76 at concentration of 2% showed as the most effective treatment in inhibiting the growth of Colletotrichum sp. (94.22%) than that of non-hydrolyzed chitosan (Suryadi et al 2016).…”
Section: Cultivationmentioning
confidence: 85%
“…The HMW chitosan was more sensitive to depolymerization (Mao et al 2004). In our previous study, a LMW of the depolymerized HMW chitosan with a high degree polymerization was successfully done using chitinase extracted from B. cepacia isolate E76 (Suryadi et al 2016). This depolymerization was based on the enzymatic hydrolysis process by breaking the chitosan bonds at 1,4-β-glycosidic site (2009).…”
Section: Chitinase Activities Of Crude and Purified Enzyme Derived Frmentioning
confidence: 99%
“…Hasil penelitian terdahulu dilaporkan bahwa aktivitas kitinase yang diperoleh dari isolat B.cepacia E.76 cukup tinggi karena bakteri kitinolitik tersebut menghasilkan enzim yang berfungsi untuk mendegradasi kitosan menjadi K-BMR, dan selanjutnya menghasilkan formulasi K-TPP yang lebih efektif dalam menghambat pertumbuhan Colletotrichum spp. (Suryadi et al, 2016;Suryadi et al, 2017).…”
Section: Hasil Dan Pembahasanunclassified
“…sebesar 94.22%, serta menekan perkecambahan spora sebesar 74.12%. Uji in vivo K-BMR yang dilakukan terhadap C. gloeosporioides pada pepaya menunjukkan penghambatan terbaik sebesar 88.88% pada konsentrasi 2%, sedangkan pada cabai menunjukkan penghambatan terbaik sebesar 55.55% pada konsentrasi 2% dan 3% (Suryadi, et al, 2016). Hasil penelitian lain juga menunjukkan bahwa pada uji in vitro, kisaran konsentrasi kitosan 0.75 -1% mampu menghambat pertumbuhan Colletotrichum spp.…”
unclassified
“…(Pangestika 2015;Purwandari 2015) dan Colletotrichum gloeosporioides (Udayanga et al 2013) yang menyebabkan busuk pada dasar buah. Menurut Suryadi et al (2016), penggunaan kitosan enzimatik sebagai edible coating efektif menghambat pertumbuhan patogen Colletotrichum sp. penyebab penyakit antraknosa dengan konsentrasi 2% pada pepaya dan konsentrasi 3% pada cabai.…”
Section: Pendahuluanunclassified